PERBEDAAN MOTIVASI BELAJAR SISWA YANG MEMBATU DENGAN YANG TIDAK MEMBATU ORANG TUA MENCARI NAFKAH KELAS VIII DI SMP 4 TANAH PUTIH - Marlina '; Sardi Yusuf Sardi Yusuf; Elni Yakub Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract This research entitle “ Difference of motivation students learning which help with don’t help parents. Earn life class VIII, ther pupose research is first for know describe of motivation students learning which hel parents earn life, second for know describe of motivation students learning which don’t help parents earn life, third for know difference between motivation students learning which help parents earn with don’t which help parents earn life. Which become sample in this research are students class VIII SMPN 4 Tanah Putih academic year 2013/2014. The method using in this research is discriptive. For collect data using enquette much fourty question. Based of solution can of poiled conclusion there are : This research find in parallel and carry theory have tell in solution. Percentage of motivation learning students SMPN 4 Tanah Putih which help parents earn life reside in high category is 29%, middle 47% and low is 24 % and then problem of motivation learning students SMPN 4 Tanah Putih which don’t help parents earn life reside in high category is 30 %, middle 49 % an low 21 %. The defference s significance of 1,67 %. Key words : Learning Motivation